Lab-on-a-chip with fluid acoustic microagitation : piezoelectric polymer β-PVDF used as ultrassonic transducer - Cardoso, V. F. (2008)
The main objective of this article is to describe the development of a fully-integrated disposable lab-on-achip for point of care testing and monitoring of biochemical parameters in biological fluids. The lab-on-achip is composed mainly by two dies: the fluid and the detection. The fluid die, fabricated in SU-8, comprises three microfluidic cuvettes, containing the fluids into analysis, and a β-PVDF microagitation system. The detection die is fabricated in a CMOS standard process and contains the photodetectors and the electronics for signal actuation and detection. The main innovation of this lab-on-a-chip is the application of an acoustic microagitation technique by the deposition of the β-PVDF piezoelectric polymer underneath the microfluidic structures, with automatic electronic control. This piezoelectric polymer produces mechanical vibrations, which allow the enhancement of the mixing and the reaction.